A HANSENÍASE NO MATO GROSSO DO SUL: Período pré e pós-pandemia de Covid-19 - Ana Paula Caserta Tencatt Abrita (2024)
This work aimed to investigate the impact of the Covid-19 pandemic on the leprosy notification rate in Mato Grosso do Sul, from 2017 to 2022. This is a quantitative, retrospective, descriptive and correlational study. All leprosy diagnosis notifications made in Mato Grosso do Sul and in the reference unit for the treatment of the disease, Hospital São Julião, located in Campo Grande, MS in the period from 2017 to 2022, were analyzed. of Indicators and Basic Data on Leprosy in Brazilian municipalities, based on the Notifiable Diseases Information System – SINAN, and a database based on the Compulsory Leprosy Notification Forms carried out by Hospital São Julião, Campo Grande, MS. The data were analyzed descriptively and statistically using the SPSS version 23.0 software, while the disease spatialization maps in the Mato Grosso do Sul territory were developed using the Qgis 3.28.9 software. Regarding the sociodemographic profile of the cases, there was a predominance of multibacillary, male and working age patients. There was a statistically significant decrease in the comparison analysis between the number of leprosy notifications in the pre- and post-pandemic period at the national, state and reference hospital levels. A difference was also identified regarding the degree of physical disability (GIF), with a higher proportion of cases with grade 0 pre-pandemic and grade 1 post-pandemic (p=0.003). Such data point to the possibility of underreporting of leprosy cases in the state of Mato Grosso do Sul, reinforcing the need to strengthen actions aimed at identifying and diagnosing cases, in order to reduce sequelae caused by the untreated disease and mitigate losses in the regional socioeconomic scope.